STUDENTS’ ASSESSMENT OF THE UNIVERSITY EDUCATION QUALITY: EXPERIENCE AND PROSPECTS - Ковтун, О.; Сидоренко, С. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
In today’s Ukraine, essential improvement of the quality of university education is an imperative that will decide the country’s future in the European and world community. The desire to be competitive on the labour market brings gifted Ukrainian school-leavers to those universities which they think can satisfy their need in a high-quality education. Hence, the future of Ukrainian universities directly depends on their raising the quality of the educational services they offer. Such work cannot be effective without taking into consideration the opinion of students, the major consumers of these educational services. The aim of this paper is to share the experience of students’ assessment of the quality of educational services at the National Aviation University, Ukraine, and to outline prospects of such assessment. While analyzing the quality of education it is essential to turn attention to its process component, which comprises the atmosphere in the university, management and strategic planning, self-assessment and self-improvement, methods and technologies of learning and teaching, academics’ load, cooperation with stakeholders, staff and students’ mobility, students’ involvement in R&D, openness, communication, etc. The first step in conducting students’ assessment of the education quality is an independent anonymous questionnaire focusing on the major aspects of the study process, such as the quality of the academia, educational environment, facilities and resources, academic integrity and competitive professional opportunities after graduation. Every university keen on improving its quality standards should develop effective tools to integrate the students’ opinion into their internal system of quality assurance. Such mechanisms are to provide analysis and interpretation of the results of the students’ assessment and ensure that corresponding adjustments are introduced in the educational process. Taking into account inertia of many university authorities and their reluctance to hear their students’ opinion, the feasibility of real changes in education quality largely depends on increasing the role of student self-governing organizations in the university decision-making policies.